Proposta de um compensador híbrido de reativos para o controle de tensão em redes de distribuição - Nunes, Weder Tótola (2011)
This work proposes a hybrid reactive compensator to control the voltage in secondary distribution networks and improve the quality of electric energy. Strategies are defined to control the electric voltage level at the point of common coupling using techniques such as decomposition of voltage in its positive, negative and zero sequence components, applying to them different controls, passives and actives. The positive sequence is compensated with switched capacitor banks, getting different levels of reactive energy. In another way, negative and zero sequence components are compensated with a DS-STATCOM that operates without affecting the positive sequence. In addition, a procedure to project the controllers of sequence components is presented. Several cases of unbalanced loads and different power factor loads are analyzed and ther simulation results and comments are presented.